OnabotulinumtoxinA in the treatment of refractory chronic cluster headache - Lampl, Christian (J Headache Pain, 2018)
BACKGROUND: Cluster headache (CH) is a clinically well-defined primary headache disorder, approximately 20% of cluster headache sufferers experience recurrent attacks without periods of significant remission. For the treatment of chronic cluster headache (CCH) only limited therapeutic options are available. METHODS: A potential refractory CCH patient group was identified according to the clinical definition of rCCH based on the consensus statement of the European Headache Federation (EHF). Treatment with OnabotulinumtoxinA (BoNT-A; Botox®, 150 Allergan IU) was done according to the PREEMPT study protocol. A standardized headache diary was used for recording frequency, duration of attacks and pain intensity. To assess personal burden the HIT-6 and the Hospital Anxiety and Depression scale was used. Primary outcome measure was a > 50% reduction in headache minutes. RESULTS: Seventeen male patients suffering from rCCH, aged 32 ± 11 (mean ± SD) years, presenting a mean disease duration of 6.6 years completed the study of 28 weeks. The cut-off point of > 50% reduction in headache minutes as positive result was reached in 58.8%, 29.4% experienced an improvement of 30–50%. Mean frequency of headache days dropped from 28.2 to 11.8 days at week 24 (p = 0.0001; 95% CI -21.33 to − 11.61;). Intensity of remaining attacks was also reduced significantly. Headache disability scores showed a trend to improvement after BoNT-A. CONCLUSIONS: Encouraging results for the treatment with BoNT-A in rCCH patients were observed in our study population.